The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jsbm.12242
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Entrepreneurial Passion and Creativity in Developing Entrepreneurial Intentions: Insights from American Homebrewers

Abstract: The study investigates the role of entrepreneurial passion and creativity as antecedents of entrepreneurial intentions, applying social cognitive theory as an underpinning framework. Specifically, this research focuses on American homebrewing, seen as a potential incubator for entrepreneurs. Results demonstrate entrepreneurial passion having a strong positive relationship with entrepreneurial intentions, even when entrepreneurial self-efficacy is introduced as a mediator. Conversely, the relationship between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
345
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(432 citation statements)
references
References 81 publications
(113 reference statements)
24
345
0
7
Order By: Relevance
“…Subsquent research has proposed that entrepreneurial passion is an antecedent of entrepreneurial intentions (Biraglia and Kadile 2016), an outcome of entrepreneurial effort (Gielnik et al 2015), is transferable from the entrepreneur to employees (Cardon 2008), influences angel investing (Mitteness, Sudek, and Cardon 2012), mediates the relationship between self-efficacy and persistence (Cardon and Kirk 2015), and can influence entrepreneurial cognition (Cardon et al 2009). Although the influences of affective states in general and entrepreneurial passion in particular on entrepreneurial cognition have been recognized in the literature, there is little evidence of their roles in entrepreneurial learning.…”
Section: The Importance Of Entrepreneurial Passion In Cognitive Trainingmentioning
confidence: 99%
“…Subsquent research has proposed that entrepreneurial passion is an antecedent of entrepreneurial intentions (Biraglia and Kadile 2016), an outcome of entrepreneurial effort (Gielnik et al 2015), is transferable from the entrepreneur to employees (Cardon 2008), influences angel investing (Mitteness, Sudek, and Cardon 2012), mediates the relationship between self-efficacy and persistence (Cardon and Kirk 2015), and can influence entrepreneurial cognition (Cardon et al 2009). Although the influences of affective states in general and entrepreneurial passion in particular on entrepreneurial cognition have been recognized in the literature, there is little evidence of their roles in entrepreneurial learning.…”
Section: The Importance Of Entrepreneurial Passion In Cognitive Trainingmentioning
confidence: 99%
“…Existing research has demonstrated the impact that entrepreneurial passion can have on several dimensions of entrepreneurship: entrepreneurial intention (Biraglia & Kadile, 2017), investment behavior (Cardon, Sudek, & Mitteness, 2009), entrepreneurial persistence (Cardon & Kirk, 2013), and employee commitment (Breugst, Domurath, Patzelt, & Klaukien, 2012). These studies have played an important role in contributing to an understanding of the outcomes of entrepreneurial passion, but they say little about its antecedents.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the decision-making phase, several studies have shown that entrepreneurial choice is the result of a dynamic interplay among environmental inputs, personal factors, and behavioral outcomes (Bandura, 1989(Bandura, , 2012Baron, 2007;Biraglia & Kadile, 2017). In the end-user entrepreneurial model, environmental inputs are social community requests and suggestions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%